Fear, death and resistance : an ethnography of war : Croatia 1991.-1992 - Čale Feldman, Lada (Institute of Ethnology and Folklore Research : Matica hrvatska : X-press, 1993)
The war in Croatia 1991-1992 generated an incomprehensible amountof evil and caused changes in culture which we will be able todiscern only in times to come. The articles which are chosen forthis book do not "explain" the war. The authors have, each intheir own way, tried to respond to the challenge to a scientist'stheir own war, try have used proven ways of reflection on their consiousness. They have used proven ways of reflecting on their profession, but they have also tried to find new ones by collection of "research papers on war "written by ethnologists and folklorist published in three Croatian magazines.